PERAN ORGANISASI IKATAN KELUARGA SUMBA BARAT DAYA SEBAGAI WADAH PEMERSATU WARGA SUMBA BARAT DAYA DI BALI - Arnoldus Yansen Rambi Riti; I Gede Putu Yasa; I Made Adiwidya Yowana (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2022)
This study aims to reveal the roles of the Southwest Sumba Family Association in strengthening the sense of togetherness among the people in this community and the interaction that occurs in this organization. The interaction is important for all of this organization’s efforts to help Southwest Sumba people who live in Bali increase their income. This research is a qualitative descriptive study. The subjects of this study are the organization’s administrators and members who are in Bali. The data were collected through interviews and documentation gained from five informants who were chosen because they were considered to have a lot of information about what was being studied. The techniques used in the data analysis were data reduction, data presentation, and drawing conclusions. Based on the analysis, the writer concludes that the organization functions as a forum for social interaction, mutual cooperation and friendship between members – they learn from and help each other to reduce burden of life living outside their hometowns so that they can have a better life.